Unequal entanglements: how arts practitioners reflect on the impact of intensifying economic inequality. Issue 3 (27th May 2022) - Kolbe, Kristina
ABSTRACT: This article discusses how arts practitioners reflect on their work amidst deepening economic inequality. Given the renewed interest in the social role of arts institutions under conditions of financialised neo-liberalism, the paper traces the complex ways in which economic imperatives figure in cultural practice. Drawing on interviews with UK-based gallery directors, museum curators, art consultants, and artists, I map out how austerity politics and intensifying privatisation processes have a profound impact on the workings of the sector, how they recalibrate dynamics between private and public artworlds, and how they shape processes of production and curation. My data specifically document how increasing economic precarity brings into relief structural inequalities of gender, race and (post)-colonial legacies already manifesting in the artworld. Rather than understanding austerity as a financial condition only, the paper thus presents an empirical exploration of the wider inequalities that it has exacerbated, from arts funding to institutions' programming practices.